The badli system in industrial labour recruitment: manager's and worker's strategies in Calcutta's jute industry - Haan, Arjan de (1999)
This paper discusses the system of badli' (substitute) labour in the jute industry of Calcutta. This is placed in the context of recent debates about the need for flexible labour markets, and against the background of the industry's deep crisis. The paper aims to contribute to these debates by analysing the way the system of badli labour has evolved. It argues against one-sided and anachronistic interpretations that isolate employers' strategies; examines the specific circumstances that gave the system its particular shape; and tries to restore agency - managers' as well as workers' - into the labour historiography. Four main arguments are put forward. First, a badli system existed before it became regulated. Second, there are few signs of an employer's strategy to create a system of badli labour - though they did use it to their advantage. Third, the badli system is not accompanied by a social segmentation of the population of the industrial area. Finally, the paper re-examines the link between the badli system and the form of migration predominant in this industry, arguing that circular migration is the result of a complex set of circumstances, including rural conditions and socio-cultural views regarding the mobility of women. - Reproduced
Keywords: Jute industry - India - West Bengal; Labour market - India - West Bengal; Labour market